In Situ Gel Formation in Microporated Skin for Enhanced Topical Delivery of Niacinamide - Sonalika Bhattaccharjee; Moritz Beck-Broichsitter; Ajay K. Banga (MDPI AG, 2020)
Although used widely in cosmetic formulations, topical delivery of niacinamide (LogP = −0.35) is unfavorable by conventional means. Poly(lactide-co-glycolide) (PLGA) formulations, can undergo a sol-gel transition triggered by solvent exchange, entrapping molecules and sustaining their release. The current study aims to exploit the ability of PLGA to gel in situ and enhance the topical delivery of niacinamide in microporated skin. In vitro drug permeation studies were performed using vertical Franz diffusion cells. Microporation was performed using Dr. PenTM Ultima A6, where pre-treatment with a 1 mm needle-length for 10 s and a 0.5 mm needle-length for 5 s, both at 13,000 insertions/min were compared. The effect of different grades of PLGA, EXPANSORB® DLG 50-2A ("low" molecular weight), and EXPANSORB® DLG 50-8A ("high" molecular weight) on topical delivery was also determined. Formulations containing PLGA resulted in successful gelation in situ on application over microporated skin. A significantly higher amount of drug was found in the skin with the 0.5 mm treatment for 5 s (892 ± 36 µg/cm2) than with 1 mm for 10 s (167 ± 16 µg/cm2). Hence, the different grades of PLGA were evaluated with 0.5 mm, 5 s treatment, and a significantly larger amount was seen in skin with the higher rather than the lower molecular weight polymer (172 ± 53 µg/cm2).